Concentration‐dependent stimulation of melanin production as well as melanocyte and keratinocyte proliferation by melatonin in human eyelid epidermis. Issue 5 (22nd January 2023) - Sevilla, Alec; Chéret, Jérémy; Lee, Wendy; Paus, Ralf
Abstract: It remains unclear how the multifunctional indoleamine neurohormone, melatonin, alters melanin production and melanocytes within intact human epidermis under physiologically relevant conditions. In the current pilot study, we aimed to clarify this in long‐term organ‐cultured, full‐thickness human eyelid skin, selected for its clinically recognized sensitivity to pigmentation‐modulatory hormones. Warthin‐Starry histochemistry showed that 100 μM melatonin significantly increased epidermal melanin content and melanocyte dendricity after 6 days of organ culture, even though tyrosinase activity in situ was inhibited, as assessed by quantitative immunohistomorphometry. While the higher melatonin dose tested here (200 μM) did not change epidermal melanization, but again inhibited tyrosinase activity, it increased the number and proliferation of both gp100 + epidermal melanocytes and keratinocytes as well as protein expression of the premelanosomal marker, gp100, ex vivo. Contrary to most previous studies, these eyelid skin organ culture results suggest that long‐term melatonin application exerts overall stimulatory, dose‐dependent effects on the epidermal pigmentary unit within intact human skin, which appear surprisingly tyrosinase‐independent. While these provocative preliminary findings require further work‐up and independent confirmation, they encourage one to systematically explore whether prolonged melatonin therapy can (re‐)stimulate melanogenesis and increase the pool/activity of epidermal melanocytes in hypopigmented skin lesions.